Avaliação de repertórios matemáticos básicos de indivíduos com síndrome de Williams - Palombarini, Livia dos Santos (Universidade Federal de São Carlos, 2019)
Williams syndrome is a genetic disorder marked by the deletion of approximately 25 genes on chromosome 7q11.23. In addition to typical facial features, Williams's syndrome is marked by an asymmetric cognitive profile in which the development of verbal abilities are comparable to typically developing individuals while presenting a large deficit in visuospatial skills. It is hypothesized that visuospatial skills’ deficits account to the poor performance in mathematical tasks reported in individuals with Williams syndrome. Studies suggest that Williams syndrome individuals perform better in mathematical tasks that require the use of verbal skills than those that require the use of visuospatial skills. However, the results are divergent. The presence of anxiety disorders is also common in individuals with Williams syndrome. It is suggested that students with learning difficulties have a greater tendency to develop mathematics anxiety. The current study investigated whether Williams syndrome individuals perform better in mathematical tasks that require the use of verbal skills than in those that require visuoespatial skills. The performance of three individuals with Williams syndrome and six typical developing children aged between seven and 10 years were evaluated in the following mathematical domains: counting, symbolic number magnitude representation, non symbolic number magnitude representation, number transcoding, place value, number line, number fact and problem resolution. To investigate the participants’ conceptions towards mathematics and their level of mathematics anxiety, two scales were applied to obtain the participants’ equivalent receptive vocabulary age. The results corroborate with those reported in the literature and suggest that the performance of individuals with Williams syndrome in tasks requiring the use of verbal skills is slightly better than in tasks requiring the use of nonverbal skills. In general, the mathematical skills of individuals with Williams syndrome resembled those of seven-year-olds. Furthermore, the results indicate that there is no relation between PPVT-R performance and performance in verbal mathematical tasks for these participants. The conceptions and levels of anxiety obtained by the applied scales suggest that individuals with Williams syndrome in this study have no greater tendency to develop mathematics anxiety.
Evaluation of basic mathematical skills of Williams syndrome individuals
Keywords: Síndrome de Williams; Habilidades matemáticas; Habilidades verbais; Habilidades visoespaciais; Ansiedade à matemática; Williams syndrome; Mathematical skills; Verbal skills; Visuospatial skills; Mathematics anxiety; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO